Gender Equality and Divorce: Legal Guarantees of Women's Rights and Their Misuse in Traditional Muslim Communities - Sufyan, Akhmad Farid Mawardi; Kamil Strzępek (Journal of Indonesian Constitutional Law, 2025)
The divorce rate in Madura over the past three years has increased to thousands of cases. Notably, 70% of the causes can be attributed to divorce suits filed by wives. This indicates that Madura, as a traditional Muslim community, has become more sensitive to and aware of the importance of women's and wives' rights within the household. As a result, husbands must take full responsibility for their families. This study employs empirical legal research methods within a socio-legal and anthropo-legal approach and was conducted in four districts in Madura. The results show that women's awareness of their rights as wives in the four districts of Madura has increased significantly. This factor has also led wives to file for divorce because their husbands have not fully fulfilled their obligations. These lawsuits are interesting because they can be comprehensively and contextually understood based on religious arguments against divorce and the position of women who file for divorce. This study contributes to efforts to promote gender equality in the household by ensuring that the rights and obligations of husbands and wives are fully upheld, as these rights are guaranteed in the constitution, positive law, and Islamic law. Any form of neglect in fulfilling these rights has the potential to demean women and ultimately lead to divorce.